2017
DOI: 10.1002/mop.30850
|View full text |Cite
|
Sign up to set email alerts
|

1.5 µW wake‐up‐receiver for biotelemetry applications

Abstract: 16] Gielis JA. A generic geometric transformation that unifies a wide range of natural and abstratic shapes. Am J Bot. 2003;90 (3):333-338.[17] Wentworth SM. AbstractThis article presents a microwave wake-up receiver for biotelemetry applications. The circuit is designed using 130 nm CMOS technology and it consists of a passive amplification front end filter, envelope detector and baseband frequency amplifier with variable feedback filtering. The receiver is designed to operate at 7.6 GHz and measured results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In [23] it is found that the sensitivity signal-to-noise ratio (SNR) of an envelope detection circuit can be expressed as…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In [23] it is found that the sensitivity signal-to-noise ratio (SNR) of an envelope detection circuit can be expressed as…”
Section: Sensitivitymentioning
confidence: 99%
“…In [23] it is found that the sensitivity signal‐to‐noise ratio (SNR) of an envelope detection circuit can be expressed as SNR=is2in2=Vnormals4Cenv10knormalBTVnormalT2 where in2 and vn2 are the thermal noise power expressed by current or voltage, respectively, and referred to the receiver input. Vs is the amplitude of the input signal voltage, Cenv is the enveloped detection capacitor, kB is Boltzmann's constant, T is the temperature in Kelvin, and VT is the thermal voltage.…”
Section: Circuit Designmentioning
confidence: 99%
“…The receiver portion for FM‐UWB is based on an RF amplifier or filter that introduces a slope in the frequency response. The amplifier or filter converts the FM wireless signal to an amplitude‐modulated signal from which the sub‐carrier is recovered using an envelope detector such as described and utilised in [16] or [17]. State‐of‐the‐art receivers have power consumptions of 432 and 580 μW with sensitivities of −70 and −80 dBm in [9, 14], respectively.…”
Section: Introductionmentioning
confidence: 99%